Efektivitas Sistem Pembelajaran Fisika Berbasis Google Classroom untuk Meningkatkan Motivasi Belajar Peserta Didik - Sukesti, Ria; Sulisworo, Dwi (Jurnal Penelitian Pembelajaran Fisika, 2021)
The purpose of this study was to determine the effectiveness of the Google Classroom-based physics learning system to increase students' learning motivation. This research was conducted in class X high school (SMA). The research method used was pre experiment using one group research design pre test post test. The results of the implementation of Google Classroom in physics learning showed that there was an increase in student learning motivation by 14.8% and got an average response value of students of 80.8%. Google Classroom is a learning management system (LMS) that is used as a learning innovation in physics learning where its use is uncomplicated, not costly, and efficient. The Google Classroom application is the right solution in facing the era of the industrial revolution 4.0 where technology is developing so significantly. The features contained in Google Classroom are easy to use to increase students 'learning motivation, it can be concluded that the Google Classroom-based learning system is effective in learning physics and can increase students' learning motivation.Keywords: LMS, learning innovation, google classroom, physics, learning motivation.